Quarterlife Crisis Pada Masa Dewasa Awal di Pekanbaru - Icha Herawati; Ahmad Hidayat (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2020)
The transition from adolescents to adult challenges is different from the challenges of life in the previous development process. Towards the age of 25, individuals face a new life such as work, marital status, and mindset. The quarter-life crisis is a phenomenon that is common in individuals aged 20-30 years old. The crisis of a quarter of a century, that's how the term counts with individuals who attend 25 years. The quarter-life crisis experiences’ by individuals grew up. This research is descriptive quantitative research. The subjects in this study consist of 236 adults in Pekanbaru who attended for 20-30 years. The retrieval of data in this study uses the quarter-life crisis scale. The results showed that the early adult individual quarter-life crisis in Pekanbaru reached 43.22%, increasing the high category of 27.97%. The results showed the fact that factors affecting the quarterly life crisis estimated as gender, status, and occupation. The conclusions of this study show that adults in Pekanbaru who spend a quarter of life issued by women, are single and do not have jobs.